VIOLATION OF GRICE’S MAXIMS IN ONLINE CLASSROOM DISCUSSION: IMPLICATIONS FOR STUDENT-LECTURER INTERACTION DYNAMICS - Sinta Dewi; Xena Dwi Aurora; Citra Yuliani; Yustika Nur Fajriah (Perkumpulan Madani Publisher Indonesia, 2025)
This study explores the violation of Grice’s Maxims in a sophomore online academic writing class and examines their implications for student–lecturer interaction dynamics. In the context of online learning, miscommunication is more likely due to the absence of physical cues and asynchronous communication patterns. Using a qualitative descriptive approach, data were collected through classroom observation and semi-structured interviews with one lecturer and three students selected via purposive sampling. Instances of maxim violations were identified and analyzed using thematic analysis based on Grice’s theoretical framework. The findings revealed that the most frequently violated maxims were Quantity and Manner, often due to vague, minimal, or hesitant student responses. Violations of Relevance and Quality also occurred, especially when responses were off-topic or lacked evidential support. Factors contributing to these violations included linguistic insecurity, abstract question formulation, technical disruptions, and limited non-verbal interaction. Interestingly, the lecturer sometimes intentionally flouted maxims to reduce student anxiety and facilitate participation. These findings highlight the complexity of digital communication and the importance of pragmatic awareness in virtual classrooms. The study underscores the need for adaptive pedagogical strategies that foster clarity, engagement, and mutual understanding. It also contributes to the broader discourse on online pragmatics by illustrating how maxim violations, while seemingly disruptive, can serve functional and pedagogical roles in shaping effective communication within digital academic environments.